2022
DOI: 10.21203/rs.3.rs-1901203/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anomalous optical response of graphene on hexagonal boron nitride substrates

Abstract: Graphene/hBN heterostructures can be considered as one of the basic building blocks for the next- generation optoelectronics mostly owing to the record-high electron mobilities. However, currently the studies of optical properties of graphene are limited to the standard substrates (SiO2/Si, glass, quartz) despite the growing interest in graphene/hBN heterostructures. This can be attributed to a challenging task of the determination of hBN’s strongly anisotropic dielectric tensor in the total optical response. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The use of vdW heterostructures for optical engineering has also been suggested by recent theoretical research [33][34][35][36]. Several studies have also reported that when Gr is included in heterostructures, its intrinsic absorption can grow by up to 60% [37,38]. These results raise the fundamental question of non-additive optical effects in heterostructures (Figure 1a).…”
Section: Introductionmentioning
confidence: 60%
“…The use of vdW heterostructures for optical engineering has also been suggested by recent theoretical research [33][34][35][36]. Several studies have also reported that when Gr is included in heterostructures, its intrinsic absorption can grow by up to 60% [37,38]. These results raise the fundamental question of non-additive optical effects in heterostructures (Figure 1a).…”
Section: Introductionmentioning
confidence: 60%